Factors that affecting inflation rate in United States / Nur Fadhlin Rashid - Rashid, Nur Fadhlin (Faculty of Business and Management, 2018)
Inflation is one of important serious matter that needs to be focus on. The aim of this factor is to determine the factors that affecting inflation rate in United States. This research has been conducted by collecting and searching data from the articles, annual report and trusted sites. The period of this study is 30 years which is from 1987 until 2016 which only focus in United States. In this research, unit root test, descriptive statistic, correlation analysis and multiple linear regressions are run to investigate the relationship between independent variable and the dependent variable, which is between, unemployment rate, household consumption, crude oil prices and money supply. From this study, household consumption and brent crude oil has positive significant relationship with inflation rate. While, for unemployment rate and money supply, there are negative significant relationship with inflation rate.